Pulse-extended excimer laser crystallisation of Pb(Zr,Ti)O 3 thin films for integration on low thermal budget substrates - Donohue, P. P.; Todd, M. A.; Huang, Zhaorong (Taylor and Francis, 2003)
Excimer laser annealing has been used to convert low temperature (non-ferroelectric) deposited lead zirconate titanate (PZT) to the perovskite phase without significantly heating underlying layers. A pulse-extension technique has been used to lengthen the laser pulse duration from 25 ns to 374 ns, lowering the surface temperature and improving the heat distribution in the PZT, as compared to the non-extended case, but still not significantly heating the substrate. Initial experiments are reported which have shown the technique to be capable of crystallising over half a 500 nm thick PZT film to perovskite although a melting effect limited the converted thickness. The thickness crystallised is however of the order of that used in FeRAM devices and modelled temperature profiles suggest that the technique provides a tractable solution for high temperature processing of ferroelectric thin films of thickness 200-300 nm on low thermal budget substrates.
Keywords: Laser annealing; pulse-extension; ferroelectric; PZT; thin film